PENGAWASAN IZIN TRAYEK ANGKUTAN UMUM DI KABUPATEN KUANTAN SINGINGI TAHUN 2016 - Rino Antoni; Erman M (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Not a few private vehicles that are used as public vehicles are operated in Kuantan Singingi Regency which is not in accordance with the established rules, as set out in Law Number 2 of 2009. Some private cars are not licensed as public transportation.Unlicensed transport routes are private / private cars with black plates.The formulation of this research problem is how the supervision of public transport route permit in Kuantan Singingi Regency in 2016 .This study aims to determine the supervisionpublic transport route permitin Kuantan Singingi Regency .This research uses qualitative research method with descriptive research type.This method aims to get a true picture of the route permit monitoring.This research finds that direct supervision conducted by the Department of Transportation Kuantan Singingi Regency done by working together with the police conduct razia street.The vehicles that were caught in the raid were given ticket and then followed up in court for termination of sanction in accordance with the violation committed.Indirect supervision by the Department of Transportation Kuantan Singingi District conducted by way of data collection public transportation operating in Kuantan Singingi.In addition, the Department of Transportation conducts evaluations and reports that are conducted every month as a form of accountabilityanswers to the tasks performed.Keywords:Monitoring, Route Permit,PublicTransport